2007
DOI: 10.1619/fesi.50.449
|View full text |Cite
|
Sign up to set email alerts
|

On Global Attractors for a Nonlinear Parabolic Equation of m-Laplacian Type in RN

Abstract: Abstract. We prove the existence, some absorbing properties and some regularities of ðL 2 ðR N Þ; L p ðR N ÞÞ, 2 a p < y, global attractor for the m-Laplacian type quasilinear parabolic equation in R N with a perturbation gðx; uÞ þ f ðxÞ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Here we use the facts Then by definition E w (t) and (17) By applying Lemma 2.1 we can derive (13). So we prove that S(t) is asymptotically smooth.…”
Section: Lemma 32 Under the Hypotheses (H1) − (H3) S(t) Is Asymptomentioning
confidence: 90%
See 1 more Smart Citation
“…Here we use the facts Then by definition E w (t) and (17) By applying Lemma 2.1 we can derive (13). So we prove that S(t) is asymptotically smooth.…”
Section: Lemma 32 Under the Hypotheses (H1) − (H3) S(t) Is Asymptomentioning
confidence: 90%
“…In [17], the authors showed the existence of global attractor for plate equation with nonlinear damping. In [13,14], the authors dealt with the global attractor for nonlinear parabolic equation of mLaplace type in R N . Recently, the research of beam equations have attracted considerable attention(see [1,2,4,5] and reference there in).…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is working in usual Sobolev spaces (cf. [12,21,23,24,25]). By combining the decomposition of the solution and the tail cut-off technique, Belleri and Pata [4] obtained the existence of global attractor for the strongly damped wave equation on R 3 :…”
mentioning
confidence: 99%